1998
DOI: 10.1590/s0102-76381998000300002
|View full text |Cite
|
Sign up to set email alerts
|

Revascularização do miocárdio com cirurgia minimamente invasiva (MIDCAB): resultados em 46 pacientes

Abstract: Objetivo: Apresentar a experiência com a realização de revascularização do miocárdio com técnica minimamente invasiva, via minitoratocotomia anterior esquerda sem circulação extracorpórea (MIDCAB). Casuística e Métodos: 46 pacientes foram submetidos a MIDCAB de fevereiro de 1997 a janeiro de 1998. Todos eram portadores de doença obstrutiva na porção proximal do ramo interventricular anterior (RIA). A técnica consistiu em pequena incisão, de cerca de 8,0 cm, transversal, na região inframamária esquerda, obtendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…The on-pump surgery leads to less cell injury compared with the conventional method of CABG surgery, and normal blood troponin level is not certain clue of patent grafts. The opposite is also true, or that is, high levels do not necessarily indicate that the graft is occluded, but only that there was a significant myocardial injury during or after the procedure [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The on-pump surgery leads to less cell injury compared with the conventional method of CABG surgery, and normal blood troponin level is not certain clue of patent grafts. The opposite is also true, or that is, high levels do not necessarily indicate that the graft is occluded, but only that there was a significant myocardial injury during or after the procedure [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Com o acesso subxifoide, evitando-se os espaços intercostais, diminuiria a dor, evitaria o maior prejuízo na função pulmonar e o paciente teria melhor condição de cooperar com o importante papel do fisioterapeuta no PO. A realização de RM com abordagem menos invasiva provavelmente propicia menores custos hospitalares pelo decréscimo nos dias de internação 30 .…”
Section: Discussionunclassified
“…Buffolo et al 35 reported that no difference existed with or without extracorporeal circulation in regard to the occurrence of infection and the incidence of perioperative acute myocardial infarction. They also reported that the incidence of pulmonary complications due to surgery was 9.7% for the group using extracorporeal circulation versus 3.2% for the group not using extracorporeal circulation.…”
Section: Discussionmentioning
confidence: 99%